Code Switching in Sarah Sechan Talk Show on NET TV - Dyah Puspitasari, Ratna; Dewanti, Anna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to analyze the type and functions of code switching used by the presenter in Sarah Sechan Talk Show on NET TV. The main theory used is type and reason of code switching by Holmes (2013). The qualitative method was used and the data were transcriptions of three episodes chosen in the show. The data were obtained by downloading the video of the program on Zulu.id and transcribing the utterances in written form. After analyzing the data, the writer classified the utterances based on two types of code switching.